Intra-annual dynamics of phloem formation and ultrastructural changes in sieve tubes in Fagus sylvatica. (19th September 2018) - Prislan, Peter; Mrak, Polona; Žnidaršič, Nada; Štrus, Jasna; Humar, Miha; Thaler, Nejc; Mrak, Tanja; Gričar, Jožica
Abstract: Despite increased interest in the timing and dynamics of phloem formation, seasonal changes in the structure of phloem sieve elements remain largely unexplored. To understand better the dynamics of phloem formation and the functioning of sieve tubes in the youngest phloem in Fagus sylvatica L., we investigated repeatedly taken phloem samples during the growing season of 2017 by means of light microscopy, and transmission and scanning electron microscopy. Phloem formation started with the expansion of the overwintered early phloem sieve tubes adjacent to the cambium and concurrent cambial cell production. The highest phloem growth rate was observed in general 1 week after the onset of cambial cell production, whereas the transition from early to late phloem occurred at the end of May. Cambial cell production ceased at the end of July. The final width of the phloem increment was 184 ± 10 μm, with an early phloem proportion of 59%. Collapse of older phloem tissue is a progressive process, which continuously occurred during the sampling period. Collapse of early phloem sieve tubes started shortly after the cessation of cambial cell production. Prior to the onset of radial growth, late phloem from the previous year represented 80% of the total non-collapsed part; during the growth period, this percentage decreased to 20%. Differences were observed in both sieve tube ultrastructure and sieve plate geometry between the youngest and older phloem. However, sieve plates were never completely occluded by callose, suggesting that processes affecting the functionality of sieve tubes may differ in the case of regular collapse or injury. The youngest parts of the phloem increment from the previous year (i.e., previous late phloem) continue functioning for some time in the current growing season, but the two-step development of overwintered phloem cells also ensures a sufficient translocation pathway for photosynthates to the actively growing tissues.